Bioactive and adhesive properties of multilayered coatings based on catechol-functionalized chitosan/hyaluronic acid and bioactive glass nanoparticles - Almeida, Ana Catarina (2020)
Chitosan and hyaluronic acid are themost attractive natural polysaccharides used for tissue regeneration, herein innovative orthopedic coatings were constructed by dip-coating technique. Inspired by the tough nacre-like structure, multifunctional (MF) films were constructed using bioactive glass nanoparticles (BGNPs) as the inorganic phase and hyaluronic acid (HA) and chitosan (CHT) polymers as the organic phase. Polymeric (CTR) films were also builtwith both polysaccharides. Inspired by the marine mussel's adhesive proteins, itwas the first time that multilayered coatings containing both HA and CHT catechol conjugates were combined with BGNPs. Both catechol-conjugates were successful synthesized and, particularly for HA, it was possible to achieve the double of the substitution degree varying the reaction time. Prior to the LbL build-up, viscosity and Zeta potential measurements of the polyelectrolytes were conducted. The in-situ LbL growth of the films was monitored by quartz crystalmicrobalance with dissipation monitoring. Itwas found that the combination of both catechol conjugates resulted in amore compact LbL structure. Itwas also shown thatMF evidenced bioactivity, CTR presented an improved adhesion, and preliminary cellular tests confirmed the biomedical potential of these multilayered coatings being used in orthopedic implants.